Selective oxidation of 5-hydroxymethylfurfural with H2O2 catalyzed by a molybdenum complex. Issue 7 (9th December 2015) - Li, Shuang; Su, Kunmei; Li, Zhenhuan; Cheng, Bowen
Abstract : A molybdenum complex exhibited excellent performance in 5-hydroxymethylfurfural oxidation with H2 O2 . Abstract : Organic solvent free 5-hydroxymethylfurfural (HMF) oxidation into 2, 5-furandicarboxylic acid (FDCA) with hydrogen peroxide using quaternary ammonium octamolybdate and quaternary ammonium dectungstate was studied. Tetra-1-ethyl-3-methylimidazolium octamolybdate ([EMIM]4 Mo8 O26 ), tetra-hexadecyltrimethyl ammonium octamolybdate ([CTAB]4 Mo8 O26 ) and tetra-ethylpyridinium octamolybdate ([EPy]4 Mo8 O26 ) displayed high activity for the selective oxidation of HMF to FDCA, and the selectivity of FDCA could reach 100% with a 99.5% conversion of HMF in the presence of [EMIM]4 Mo8 O26 . The byproduct formed in competition with FDCA was identified as the intermediate 5-hydroxymethyl-2-furan carboxylic acid (HMFCA) and 5-formyl-2-furan carboxylic acid (FFCA), and neither 2, 5-diformyl furan (DFF) nor any other byproducts from the oxidative cleavage of the HMF furan ring were detected during the oxidation process, which indicated that the aldehyde group of HMF oxidizes first, followed by the oxidation of the hydroxymethyl group in this reaction system. Although the quaternary ammonium salts, such as [EMIM]Br, EPyBr and CTAB, prevented FDCA formation from the HMFCA advanced oxidation, they could eliminate the oxidative cleavage of the furan ring and improve the affinity of HMF and catalysts, to make the catalytic active centers readily accessible to HMF molecules. However, tetra-1-ethyl-3-methylimidazolium dectungstate ([EMIM]4 W10 O32 ), tetra-hexadecyltrimethyl ammonium dectungstate ([CTAB]4 W10 O32 ) and tetra-ethylpyridinium dectungstate ([EPy]4 W10 O32 ) were unfavorable for FDCA formation. The great difference in performance of quaternary ammonium octamolybdate and quaternary ammonium dectungstate in HMF oxidation with H2 O2 was attributed to their different structure.